A preliminary report on certain aspects of the biology of the South African anchovy, Engraulis capensis (Gilchrist) - Robinson, Gilbert Adrian (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1966.